Assessment of Outcome During Hospital Stay in Patients with Decompensated Chronic Liver Disease with Sepsis Using PT-INR To Albumin Ratio (PTAR) Score in a Tertiary Care Hospital of Puducherry - Augusteen Pilli; Stanley Ambroise; Sivaramakrishnan Patchaiyappan (National Board of Examinations Journal of Medical Sciences)
Background: Decompensated chronic liver disease with sepsis is a life-threatening condition and associated with high mortality. Early risk stratification using reliable prognostic score is essential. So, this study aims to classify and assess the treatment outcome of Decompensated Chronic Liver Disease patients with sepsis based on PT-INR to Albumin ratio (PTAR) score. Methods: A Hospital based Observational study was conducted in a Government Tertiary care Hospital of Puducherry. A total sample size was calculated to be 107 and the participants those who fulfilled the eligibility criteria were included. On the day of admission PTAR score was calculated to classify the participants as Low risk (PTAR < 0.54), Medium risk (PTAR 0.54 to < 0.82) and High-risk (PTAR ≥ 0.82). Data was analysed using statistical software and chisquare test was applied to find the association between PTAR score and treatment outcome. Results: Around 108 participants were recruited and the mean age was 49.48 ± 11.28 (years). Majority of the participants were males 105 (97.2%). The treatment outcome status of the participants shows that 38 (35.2%) died and 70 (64.8%) survived on follow-up till the point of discharge. The classification of patients based on PTAR score shows that 36.1%, 35.2% and 28.7% were in high, medium and low risk category. The mean PTAR score of participants who survived was 0.68 ± 0.38 and those who died was 1.01 ± 0.48. Conclusion: PTAR was an accurate tool to predict the outcome status of the decompensated liver disease patients with sepsis. As the PTAR score increases proportionately the risk of mortality increases.